Genome‐wide association study of chemotherapeutic agent‐induced severe neutropenia/leucopenia for patients in Biobank Japan. Issue 8 (10th June 2013) - Low, Siew‐Kee; Chung, Suyoun; Takahashi, Atsushi; Zembutsu, Hitoshi; Mushiroda, Taisei; Kubo, Michiaki; Nakamura, Yusuke
Abstract : Chemotherapeutic agents are notoriously known to have a narrow therapeutic range that often results in life‐threatening toxicity. Hence, it is clinically important to identify the patients who are at high risk for severe toxicity to certain chemotherapy through a pharmacogenomics approach. In this study, we carried out multiple genome‐wide association studies (GWAS) of 13 122 cancer patients who received different chemotherapy regimens, including cyclophosphamide‐ and platinum‐based (cisplatin and carboplatin), anthracycline‐based (doxorubicin and epirubicin), and antimetabolite‐based (5‐fluorouracil and gemcitabine) treatment, antimicrotubule agents (paclitaxel and docetaxel), and topoisomerase inhibitors (camptothecin and etoposide), as well as combination therapy with paclitaxel and carboplatin, to identify genetic variants that are associated with the risk of severe neutropenia/leucopenia in the Japanese population. In addition, we used a weighted genetic risk scoring system to evaluate the cumulative effects of the suggestive genetic variants identified from GWAS in order to predict the risk levels of individuals who carry multiple risk alleles. Although we failed to identify genetic variants that surpassed the genome‐wide significance level ( P <  5.0 × 10 −8 ) through GWAS, probably due to insufficient statistical power and complex clinical features, we were able to shortlist some of the suggestive associated loci. The current study is at the relatively preliminary stage, but does highlight the complexity and problematic issues associated with retrospective pharmacogenomics studies. However, we hope that verification of these genetic variants through local and international collaborations could improve the clinical outcome for cancer patients.